Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Produksi PT. Semen Tonasa II Dan III Kabupaten Pangkep - Ardian Syam; Rina Rina; Andi Novita Paramitha (Jurnal Manajemen Riset Inovasi, 2024)
This research aims to determine the influence of work motivation and work discipline on the performance of production unit employees at the company PT. Semen Tonasa District. Pangkep. The method used in this research is a quantitative method with the number of respondents being 75 employees who were used as samples using a sampling technique, namely using a saturated sample. The analysis used in this research is a multiple linear regression test. The results of simultaneous testing of work motivation and work discipline variables have a positive and significant influence on employee performance variables as proven based on simultaneous test results with a significance value of f<α (0.000<0.05). The partial test results of the work motivation variable have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05). The partial test results of the work discipline variable have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05).